Clinical spectrum and uncommon features of McCune-Albright syndrome in children: a cohort study from a National Referral Center - Bergignat, Solène; Chapurlat, Roland; Nicolino, Marc; Perge, Kevin (Frontiers in Endocrinology, 2025)
IntroductionMcCune-Albright syndrome (MAS) is a rare disease caused by somatic gain-of-function variants in the GNAS gene that lead to constitutive activation of the G protein alpha subunit (Gsα). Pathologic consequences can involve several tissues. Fibrous dysplasia (FD), café-au-lait skin macules and hyperfunctioning endocrinopathies are classic manifestations. However, the phenotypic spectrum of MAS is considerably wider and more complex.MethodsWe performed a pediatric retrospective study from our National Referral Center between 2007 and 2021 to describe the clinical spectrum of MAS in children, with a focus on unusual or severe manifestations.Results and discussionA total of 33 children were included. Peripheral precocious puberty was the most frequent endocrinopathy, affecting 84,6% of girls and was the presenting feature for 57,6% of them. Thyroid involvement was also common, consisting in morphological abnormalities with or without slight hyperthyroidism. Thyroid nodules were typically benign, but one patient presented a follicular thyroid carcinoma. Cushing syndrome typically occurs in the neonatal period, but we observed an unusual case of hypercortisolism revealed in early infancy. FD was very common and manifested along a wide range of severity, from monostotic and asymptomatic lesion to polyostotic FD with pain, fractures, and compressive optic neuropathy. We described a locally aggressive FD involving sphenoid and maxillary bones which leaded a young female patient to death. Finally, we reported hepatic disorders, including a case of hepatocellular adenoma. In conclusion, MAS is a multisystemic disorder, with a variable combination of symptoms, and a broad range of severity. These uncommon abnormalities mostly occurred in patients with significant involvement of multiple other tissues.